2011
DOI: 10.1016/j.dnarep.2011.04.028
|View full text |Cite
|
Sign up to set email alerts
|

XPB and XPD helicases in TFIIH orchestrate DNA duplex opening and damage verification to coordinate repair with transcription and cell cycle via CAK kinase

Abstract: Helicases must unwind DNA at the right place and time to maintain genomic integrity or gene expression. Biologically critical XPB and XPD helicases are key members of the human TFIIH complex; they anchor CAK kinase (cyclinH, MAT1, CDK7) to TFIIH and open DNA for transcription and for repair of duplex distorting damage by nucleotide excision repair (NER). NER is initiated by arrested RNA polymerase or damage recognition by XPC-RAD23B with or without DDB1/DDB2. XP helicases, named for their role in the extreme s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
134
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(142 citation statements)
references
References 180 publications
(287 reference statements)
5
134
1
Order By: Relevance
“…DNA charge transport has been suggested to activate MAPK signaling. 56,57 MAPK activation was also suggested from transcriptome analysis of another NER mutant, ercc-1 39 , where we found a strong correlation between genes regulated by the PMK-1 p38 MAPK and the ercc-1 data set. Together, these results suggest that NER function is not lifespan-limiting in C. elegans partially due to an adaptive transcriptome reprogramming involving activation of p38 MAPK stress-response signaling.…”
Section: Does Accumulation Of Cyclopurines Cause the Reduced Lifespansupporting
confidence: 72%
“…DNA charge transport has been suggested to activate MAPK signaling. 56,57 MAPK activation was also suggested from transcriptome analysis of another NER mutant, ercc-1 39 , where we found a strong correlation between genes regulated by the PMK-1 p38 MAPK and the ercc-1 data set. Together, these results suggest that NER function is not lifespan-limiting in C. elegans partially due to an adaptive transcriptome reprogramming involving activation of p38 MAPK stress-response signaling.…”
Section: Does Accumulation Of Cyclopurines Cause the Reduced Lifespansupporting
confidence: 72%
“…Mutations in the human XPD helicase gene (ERCC2) lead to the genetic disorders trichothiodystrophy (TTD), Cockayne syndrome (CS), and xeroderma pigmentosum (XP) (28)(29)(30)(31). There is now evidence that mutations specifically in the iron-sulfur cluster domain of XPD result in TFIIH instability, thus leading to TTD (28,30).…”
mentioning
confidence: 99%
“…XPD, an ATP-dependent 5′-3′ helicase from the NER pathway, is a major component of TFIIH, the transcriptional and repair machinery that unwinds damaged DNA for lesion repair in NER (28,29). Mutations in the human XPD helicase gene (ERCC2) lead to the genetic disorders trichothiodystrophy (TTD), Cockayne syndrome (CS), and xeroderma pigmentosum (XP) (28)(29)(30)(31).…”
mentioning
confidence: 99%
“…Notably, premalignant skin lesions and cutaneous tumors have never been reported in TTD. It was suggested that pathological features of XP are associated with mutations that mainly affect the DNA repair activity of TFIIH, whereas those typical of TTD also impair transcription (12,(17)(18)(19).…”
mentioning
confidence: 99%
“…Notably, premalignant skin lesions and cutaneous tumors have never been reported in TTD. It was suggested that pathological features of XP are associated with mutations that mainly affect the DNA repair activity of TFIIH, whereas those typical of TTD also impair transcription (12,(17)(18)(19).To assess whether mutated TFIIH in TTD might alter the transcription of ECM-related genes (thus affecting the strength Significance Despite exhibiting different phenotypes, the UV-sensitive syndromes trichothiodystrophy (TTD) and xeroderma pigmentosum (XP) result from the same mutated genes encoding specific subunits of the DNA-repair/transcription factor TFIIH. The widely accepted notion is that XP cancer proneness results from mutations interfering with DNA repair, whereas TTD clinical hallmarks (namely, hair anomalies, physical and mental retardation, and premature aging) are because of transcriptional alterations.…”
mentioning
confidence: 99%